Podgorski kolendači s Novoga Zelanda - Šunde, Smiljana (2008)
Most immigrants from Podgora and their descendants today can be found around New Zealand's largest city, Auckland, more precisely in Oratio which was in fact founded by Podgorani at the turn of the Twentieth Century. The majority of New Zealand Podgorani speak English but this hasn't prevented them from passing down the cultural tradition of the country of their origins or to preserve their mother tongue and other religious rituals including church hymns and other folk songs sung at Christmas or to await the New Year. Some of these songs were prohibited in the homeland due to ideological barriers (the affirmation of atheism in a communist Croatia) and have only recently been revived in Podgora itself. Even though Podgorani have lived in New Zealand for more than 120 years, it seems that they only publicly performed their kolendanje about 70 years ago. Today, Podgorani are fourth and fifth generation descendants. On the last day of 1933 a group of Podgorani settled in Oratio and organised a procession to each of their houses. One of the kolendača (Kolenda signers) Marko Marinović, (the son of the late Ante) wrote a poem of that first kolenda singing – the first under the English crown – a poem of ten verses and a total of lines. The author began her research of kolenda singers and their hosts back in 1933 in New Zealand inspired by academic Jerko Bezić. With the revival of kolenda singing in Podgora in 2004 – I continued my research and writing this article. Members of the Sutikla archapella signers disclosed the beauty and entertainment of kolenda singing and crushed through the thick ice that had covered it for more than forty years – as long as Podgora was not to hear kolenda singing.
Bibliografske bilješke uz tekst ; izvori i bibliografija: 18 jed
Summary ; resumen
Keywords: Hrvati -- Iseljenici; Novi Zeland